Scanning electron microscopy for identification of local strain of Aspergillus Parasiticus and its larvicidal efficacy against Aedes Aegypti and non‐target toxicity testing on fingerlings of Hypophthalmichthys Molitrix. Issue 9 (6th June 2022) - Abrar, Amina; Abbas, Moneeza; Mehmood, Salma; Ghani, Nadia; Fatima, Ammara; Shahzadi, Rabia
Abstract: Scanning electron microscopy proved to be helpful in identification of Aspergillus parasiticus. A. parasiticus has a worldwide occurrence with high entomopathogenic efficacy against Aedes aegypti . However, assessment of pathogenic effects of entomopathogenic fungi on non‐target organisms is required to evaluate its use as bio control agent. Aim of the present research is to study the parricidal activity of the local strain of A. parasiticus (MK371710) against A. aegypti and its toxicity assessment against aquatic model organism Hypophthalmichthys molitrix. A. parasiticus was isolated from the soil of Jallo Park, Lahore. The larvicidal effect of A. parasiticus was evaluated against fourth instar larvae of A. aegypti . Hundred percent of mortality of larvae was observed after exposure to 1 × 10 7 conidia/ml of fungal suspension after 72 h post treatment. The LC50 value of A. parsiticus in 24 h post treatment and 48 h post treatment was recorded as 1.0 × 10 7 conidia/ml 2.99 × 10 5 conidia/ml, respectively. However, an in‐depth understanding safety to non‐target organisms is necessary, if we are to properly control the action of these entomopathogenic fungi under natural conditions. For the toxicity assessment fingerlings of H. molitrix were exposed to conidial suspensions of A. parasiticus . Eye pop (64%), fin hemorrhage (33%), and scale infection (30%) were the major morphological effects observed during the study. Results reveal that although A. parasiticus is highly pathogenic to dengue vector but also have significant effects on organisms other than insects and its application as biological control agent requires safety considerations. Highlights: Assessment of pathogenic effects of entomopathogenic fungi on non‐target organisms is required to evaluate its use as biocontrol agent. SEM was used to identify the microscopic view of Aspergillus parasiticus . Aim of the present research is to study the larvicidal activity of the local strain of A. parasiticus (MK371710) against Aedes aegypti and its toxicity assessment against aquatic model organism Hypophthalmichthys molitrix . Abstract : flow chart of experimental work.